Eugenol and lidocaine inhibit voltage-gated Na+ channels from dorsal root ganglion neurons with different mechanisms - Moreira-Junior, Luiz; Leal-Cardoso, Jose Henrique; Cassola, Antonio Carlos; Carvalho-de-Souza, Joao Luis (Frontiers in Pharmacology, 2024)
Eugenol (EUG) is a bioactive monoterpenoid used as an analgesic, preservative, and flavoring agent. Our new data show EUG as a voltage-gated Na+ channel (VGSC) inhibitor, comparable but not identical to lidocaine (LID). EUG inhibits both total and only TTX-R voltage-activated Na+ currents (INa) recorded from VGSCs naturally expressed on dorsal root ganglion sensory neurons in rats. Inhibition is quick, fully reversible, and dose-dependent. Our biophysical and pharmacological analyses showed that EUG and LID inhibit VGSCs with different mechanisms. EUG inhibits VGSCs with a dose–response relationship characterized by a Hill coefficient of 2, while this parameter for the inhibition by LID is 1. Furthermore, in a different way from LID, EUG modified the voltage dependence of both the VGSC activation and inactivation processes and the recovery from fast inactivated states and the entry to slow inactivated states. In addition, we suggest that EUG, but not LID, interacts with VGSC pre-open–closed states, according to our data.